Business and Corporate Social Responsibility - MARTÍ-BORBOLLA, Luis Felipe; ORTIZ-ARANGO, Francisco (Journal of Advanced Research in Management, 2017)
This paper establishes the great significance of contemplating the Corporate Social Responsibility (CSR) as a crucial element to the survival and development of business. We present the fundamental elements of the CSR regarding business, ranging from the stages and types of CSR to the social implications that come with CSR applied to business to engage social innovation, social entrepreneurship and business mentoring, including the benefits that entails carrying out CSR practices, among which are the best public perception and increased sales among other benefits.